Program Peningkatan Kemandirian Ekonomi Panti Asuhan Syifa’ul Qolbi - Risgiyanti Risgiyanti; Ana Shohibul (Bakti Cendana, 2019)
Syifa’ul Qolbi Orphanage holds supporting facility in the form of confection. In addition to a business, this confection functions as a place to train the orphans’ sewing skill. Yet the development of this business faces a number of obstacles such as traditional business management, sub-optimal marketing strategy, inefficient production tools and the training participants’ lack of motivation and entrepreneurship. This community service attempted to realize the orphanage management’s goal of developing their fashion business and developing entrepreneurship among the orphans so that they can optimize their potential in the future. Some of the programs have been held through community service. The programs were entrepreneurship workshop, pattern and design training, business management training, e-marketing training, branding and marketing concept, and business accompaniment. This community service results in the improvement of participant's motivation and entrepreneurship character, bussiness management knowledge,and skill in making pattern and design. The other results are fashion brand creation, digital marketing facility, and quality product improvement.This program also give several production equipments to help the improvement of eficiency and e